THE DEVELOPMENT OF CHILDREN’S PERSONALITIES IN WILLIAM GOLDING’S LORD OF THE FLIES - Aisyiyah Hanif Muallim (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2020)
The aims of the study were to reveal the cause of personality development on children’s characters and to elaborate the exertion in eradicating poverty reflects from the novel Lord of the Flies. This study employed descriptive qualitative study with psychoanalytical approach initiated by Sigmund Freud focused on literature as the reflection of real life. The primary data in this study were collected from the novel “Lord of the Flies” by William Golding (1954). The secondary data were taken from the library, internet, and journals, theses, and articles. The research result indicates that the personalities of the children are developed based on the anxiety and defense mechanism as part of psychoanalysis. Other finding is about the reflection of poverty eradication shows in the story. The children’s efforts in getting rescued and hunting could be the reflection of escape from poverty.